Pengembangan Model Media Smart Card Untuk Pembelajaran Bola Basket (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2016)
The purpose of this study is to find out the development product of smart card media for basketball learning to the four grade of SDIT Permata Hati Kecamatan Madukara Kabupaten. The study is a research and development. There are procedures of the product development based on this research, they are: (1) Analyse the product of the result of information collected, including field observation and theoritical review, (2) develop the form of the first product ( in form of basketball smart card media), (3) expert validation test that is an expert of basketball and an expert of physical learning and try out 1, (4) revision of the first product. This revision is used for an improvement toward the first product that is resulted by the researcher, (5) try out II, (6) revision of the last product that is done according to the result of the field try out, (7) the final result of the model of smart card media for basketball learning for the four grade of SDIT Permata Hati.The result of this research in try out I is resulted 85,3% that is categorized as good, and the result of the try out II is resulted 87,7% that is categorized as good, because the students are able to do those three aspects so it is acceptable to be used. So, it can be concluded that there is a difference between try out I and try out II that is 2,44%.